Changing channels? A comparison of Fox and MSNBC in 2012, 2016, and 2020. Issue 1 (31st July 2021) - Lanning, Kevin; Wetherell, Geoffrey; Warfel, Evan A.; Boyd, Ryan L.
Abstract: We compare the contents of Fox and MSNBC weekday evening telecasts using natural language analysis with Linguistic Inventory Word Count (LIWC) and sociopolitical dictionaries tapping into moral foundations, values, grievances, and personality. Across time, the two networks differed substantially across many constructs, particularly those from LIWC. The core of the difference between the networks was captured by a four‐component measure which we labeled Personalizing versus Formal speech. Scores on this measure were particularly volatile during 2019 and 2020, a period which included Trump's first impeachment, the beginning of the COVID pandemic, and the 2020 presidential campaign. In comparison with prior presidential election years, only MSNBC showed a drop in positive emotions in 2020, while both networks increased in the use of communal and analytic language. Contrary to our expectations, the language style of the two networks did not demonstrate increasing divergence over time.